Pemberdayaan Perempuan dalam Memanfaatkan Sampah Kresek Menjadi Produk Bernilai Ekonomis - Benedhikta Kikky Vuspitasari; Deffrinica Deffrinica; Shanti Veronnica Br Siahaan; Novita Novita (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2021)
Abstract: Plastic waste is one of the most common plastic wastes around Suka Maju village, the lack of public knowledge in utilizing and processing plastic waste into products of economic value, based on this background, the Shanti Bhuana Institute lecturer community service activity was carried out and involved two students, the purpose of this activity is to provide knowledge about the processing of plastic waste that is often found by mothers in Suka Maju village so that they get new knowledge and can be applied in their daily lives. The method used in this activity is the method of lecturing, question and answer and direct practice, the participants who attend consist of mothers, while the material is given knowledge about waste, the dangers of waste and its impacts, as well as the practice of making handicrafts. Activities carried out at the homes of local residents in the form of a workshop meeting. The results obtained were that the use of plastic which was applied in the community service activities of the Shanti Bhuana Institute was a new activity for mothers who participated in these activities, the mothers were very enthusiastic in these activities as seen from their presence in this activity Direct practice allows them to know directly how to make economically valuable products. From this activity, it can be concluded that the community service activities carried out have a good impact because some women can practice how to manufacture products by utilizing plastic waste to become economically valuable products.        Keywords: economic value; plastic waste; women empowerment  Abstrak: Sampah kresek merupakan salah satu limbah plastik yang banyak ditemui disekitar desa Suka Maju, kurangnya pengetahuan masyarakat dalam memanfaatkan dan mengolah sampah kresek menjadi produk yang bernilai ekonomis, untuk itu perlu dilakukan kegiatan pengabdian masyarakat yang dapat memberikan pengetahuan tentang pengolahan sampah kresek. tujuan kegiatan ini adalah memberikan pengetahuan kepada masyarakat tentang pengolahan sampah kresek yang banyak dijumpai oleh ibu-ibu yang ada di desa Suka Maju sehingga mereka mendapatkan pengetahuan baru dan dapat diterapkan dalam kehidupan mereka sehari-hari. Metode yang digunakan dalam kegiatan ini adalah metode ceramah, tanya jawab dan praktik secara langsung, peserta yang hadir terdiri dari ibu-ibu. Hasil yang diperoleh bahwa pemanfaatan plastik kresek yang diterapkan dalam kegiatan pengabdian masyarakat Institut Shanti Bhuana merupakan kegiatan yang baru bagi ibu-ibu yang mengikuti kegitan tersebut, ibu-ibu sangat antusias dalam kegiatan tersebut terlihat dari kehadiran mereka dalam kegiatan ini dan kegiatan praktik yang dilakukan secara langsung membuat mereka secara langsung dapat mengetahui bagaimana cara membuat produk yang bernilai ekonomis. Dari kegiatan ini dapat memberikan dampak yang baik karena sebagian ibu-ibu dapat mempraktikan cara pembuatan produk dengan memanfaatkan sampah plastik kresek menjadi produk bernilai ekonomis. Kata kunci: bernilai ekonomis; pemberdayaan perempuan; sampah kresek